Impact of Exchange Rate Changes on Domestic Inflation: The Turkish Experience - Ara Volkan; Cem Saatçioğlu; Levent Korap (Turkish Economic Association, 2007)
This paper examines the extent to which changes in exchange rates result in changes in Turkish domestic inflation. Specifically, we determine if there has been a change in the magnitude of this impact from the pre-2003 period to the post-2003, when the exchange rates were allowed to float. Employing monthly frequency data, we estimate two impulse-response functions and pass-through coefficients, one derived for the 1994 April-2002 December period using 1994 price indices as base (100) and the other one derived for the 2003January-2006December period using the 2003 price indices as base (100). We confirm that exchange rate shocks feed into domestic inflation, first at the level of manufacturers prices and then at the level of consumer prices, and that the impact of the shocks on the price variables of the various stages of the supply chain is different. Our findings indicate that the magnitude of the impact has declined for the post-2003 period by nearly one-half compared to the pre-2003 period during the early stages of the production process reflecting the predominance of the manufacturer price index in determining Turkish inflation rates. In addition, the decline in the exchange rate pass-through impact on domestic prices coincides with a 25 percent decline in the post-2003 consumer price inflation. Regardless, the consideration of the impact of exchange rate changes on the domestic inflationary process is still important when establishing monetary policies for the Turkish economy.
Keywords: 330; Wechselkurs; Exchange Rate Pass-Through; Inflation; Schätzung; Türkei